A graphical user interface integrating features from different hypertext domains - Wang, Weigang
Integration of different hypertext domains is a relatively new concern to the hypertext community. This paper presents an integrative design of graphical user interfaces of hypermedia systems. This design embraces features from navigational, spatial, taxonomic, and workflow hypertexts. The result is a visual hypertext with a rich set of visual components and user interface mechanisms.